Luck: Its Nature and Significance for Human Knowledge and Agency - Coffman, E.J. author. aut Link
XI, 202 p.
Keywords: As thinkers in the market for knowledge and agents aspiring to morally responsible action, we are inevitably subject to luck. This book presents a comprehensive new theory of luck in light of a critical appraisal of the literature's leading accounts, then brings this new theory to bear on issues in the theory of knowledge and philosophy of action.